2015
DOI: 10.1007/s10995-015-1899-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Positive Deviance to Understand the Uptake of Optimal Infant and Young Child Feeding Practices by Mothers in an Urban Slum of Mumbai

Abstract: Objectives Positive deviance research seeks out well-nourished children living in disadvantaged contexts to understand local growth-promoting behaviors. This study explored the factors that influence the uptake of infant and young child feeding behaviors among mothers. Methods Children with a height-for-age z-score (HAZ) > 0 (n = 10) or a HAZ < -2.0 (n = 12) were purposefully selected from households enrolled in a community management of acute malnutrition (CMAM) program in an urban slum of Mumbai, India. Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…In de Onis (WOE = M), infants were fed a mean of 2·8 food groups at 6 months, rising to 5·1 at 24 months (34) . Five other studies reported some information on diversity (35)(36)(37)(38)(39) . Table 3 denotes a summary of all complementary food groups identified from the studies, categorized according to the WHO IYCF food groups defined above.…”
Section: Dietary Diversitymentioning
confidence: 99%
See 4 more Smart Citations
“…In de Onis (WOE = M), infants were fed a mean of 2·8 food groups at 6 months, rising to 5·1 at 24 months (34) . Five other studies reported some information on diversity (35)(36)(37)(38)(39) . Table 3 denotes a summary of all complementary food groups identified from the studies, categorized according to the WHO IYCF food groups defined above.…”
Section: Dietary Diversitymentioning
confidence: 99%
“…Delhi (33,43,47,57,58,70,81,87,100,105) Madhya (69,106) Mangalore (80,102) Haryana (75,86) Rajasthan (52) Gujarat (28,64) Kashmir (38) Ludhiana (53) Himachal (82) Uttarakhand (48,61,77) Uttar Pradesh (36,60,71,98,103) Assam (41,104) Bihar (55,83) West Bengal (30,56,84) Odisha (Orissa) (76,78) Andhra Pradesh (42,74) Maharashtra (27,35,39,50,(66)(67)(68)101) Karnataka (44,(45...…”
Section: Dietary Diversitymentioning
confidence: 99%
See 3 more Smart Citations